2020
DOI: 10.1029/2019ja027670
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Depletions in the Nightside Martian Upper Atmosphere Revisited

Abstract: Energetic electron depletions are a notable feature of the nightside Martian upper atmosphere. In this study, we investigate systematically the variations of the occurrence of depletions with both internal and external conditions, using the extensive Solar Wind Electron Analyzer measurements made on board the Mars Atmosphere and Volatile Evolution. In addition to the known trends of increasing occurrence with decreasing altitude and increasing magnetic field intensity, our analysis reveals that depletions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Lillis et al, 2018) and, within the context of this study, increasing the portion of solar wind electrons contained in the observed suprathermal electrons. This effect was also supported by the observed modulation of energetic electron depletions in the nightside Martian ionosphere by the upstream solar wind condition (Niu et al, 2020). On the other hand, a higher solar wind dynamical pressure can compress the magnetic field lines that connect the dayside and CAO ET AL.…”
Section: Influences Of Upstream Solar Wind Conditionmentioning
confidence: 70%
See 1 more Smart Citation
“…Lillis et al, 2018) and, within the context of this study, increasing the portion of solar wind electrons contained in the observed suprathermal electrons. This effect was also supported by the observed modulation of energetic electron depletions in the nightside Martian ionosphere by the upstream solar wind condition (Niu et al, 2020). On the other hand, a higher solar wind dynamical pressure can compress the magnetic field lines that connect the dayside and CAO ET AL.…”
Section: Influences Of Upstream Solar Wind Conditionmentioning
confidence: 70%
“…Lillis & Brain, 2013;Lillis et al, 2018;Xu et al, 2016b). Here we compare in Figure 4 the spatial distribution of the photoelectron occurrence rate between high and low upstream solar wind conditions, defined with the respective solar wind dynamic pressures above and below 0.65 nPa, respectively, where the solar wind dynamic pressure from each individual MAVEN orbit is adapted from Niu et al (2020) based on the MAVEN SWIA measurements (Halekas et al, 2015). Within the sunlight regions, the occurrence rate of photoelectron measurements is near 100% under both high and low solar wind conditions.…”
Section: Influences Of Upstream Solar Wind Conditionmentioning
confidence: 99%
“…Moreover, crustal fields appear to be key in determining the occurrence of electron depletion regions in the nightside ionosphere at altitudes greater than 170 km, while no dependence on the crustal field morphology was observed for lower altitudes (Steckiewicz et al., 2015, 2017). Electron depletions are also apparently correlated with the solar wind, with a higher occurrence rate observed for low solar wind dynamic pressure (Niu et al., 2020). Crustal magnetic fields are a key factor for shaping the plasma structures in the nightside ionosphere and have been shown to substantially modulate the precipitation of energetic electrons and result in ionization (Lillis & Brain, 2013; Lillis et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More details of how to determine topology are in the methodology section in Xu et al (2019). These basic principles to identify topology have been used in many studies (e.g., Brain et al, 2007; Duru et al, 2011; Niu et al, 2020; Steckiewicz et al, 2015; Weber et al, 2017; Xu et al, 2017, 2019).…”
Section: Methodsmentioning
confidence: 99%